Prepatterning and patterning of the thalamus along embryonic development of Xenopus laevis - Bandín, Sandra; Morona, Ruth; González, Agustín (Frontiers in Neuroanatomy, 2015)
Previous developmental studies of the thalamus (alar part of the diencephalic prosomere p2) have defined the molecular basis for the acquisition of the thalamic competence (preparttening), the subsequent formation of the secondary organizer in the zona limitans intrathalamica, and the early specification of two anteroposterior domains (rostral and caudal progenitor domains) in response to inducing activities and that are shared in birds and mammals. In the present study we have analyzed the embryonic development of the thalamus in the anuran Xenopus laevis to determine conserved or specific features in the amphibian diencephalon. From early embryonic stages to the beginning of the larval period, the expression patterns of 22 markers were analyzed by means of combined In situ hybridization (ISH) and immunohistochemical techniques. The early genoarchitecture observed in the diencephalon allowed us to discern the boundaries of the thalamus with the prethalamus, pretectum, and epithalamus. Common molecular features were observed in the thalamic prepatterning among vertebrates in which Wnt3a, Fez, Pax6 and Xiro1 expression were of particular importance in Xenopus. The formation of the zona limitans intrathalamica was observed, as in other vertebrates, by the progressive expression of Shh. The largely conserved expressions of Nkx2.2 in the rostral thalamic domain vs. Gbx2 and Ngn2 (among others) in the caudal domain strongly suggest the role of Shh as morphogen in the amphibian thalamus. All these data showed that the molecular characteristics observed during preparttening and patterning in the thalamus of the anuran Xenopus (anamniote) share many features with those described during thalamic development in amniotes (common patterns in tetrapods) but also with zebrafish, strengthening the idea of a basic organization of this diencephalic region across vertebrates.